2015
DOI: 10.1016/j.devcel.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Delimited Adhesion-Independent Clustering of E-Cadherin Forms the Nanoscale Building Blocks of Adherens Junctions

Abstract: E-cadherin is the major adhesion receptor in epithelial adherens junctions, which connect cells to form tissues and are essential for morphogenesis and homeostasis. The mechanism by which E-cadherin monomers cluster and become organized in adherens junctions remains poorly understood. Here, using superresolution microscopy techniques in combination with structure-informed functional mutations, we found that loosely organized clusters of approximately five E-cadherin molecules that form independently of cis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
232
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(251 citation statements)
references
References 55 publications
18
232
1
Order By: Relevance
“…This estimation approaches the spatial resolution limit of our microscope and, therefore, may overestimate the diameter of E-cadherin clusters. The size of these puncta is similar to that of E-cadherin clusters at cell-cell contacts in A431D cells (112 nm), but larger than that of E-cadherin clusters in EphA4 cells (60 nm) (60). It is possible that E-cadherin cluster size differs in distinct cell types and at different stages of cell-cell adhesion (61), but additional studies at high resolution are required to track E-cadherin puncta size and organization over time.…”
Section: Discussionmentioning
confidence: 63%
“…This estimation approaches the spatial resolution limit of our microscope and, therefore, may overestimate the diameter of E-cadherin clusters. The size of these puncta is similar to that of E-cadherin clusters at cell-cell contacts in A431D cells (112 nm), but larger than that of E-cadherin clusters in EphA4 cells (60 nm) (60). It is possible that E-cadherin cluster size differs in distinct cell types and at different stages of cell-cell adhesion (61), but additional studies at high resolution are required to track E-cadherin puncta size and organization over time.…”
Section: Discussionmentioning
confidence: 63%
“…The K 2D values of WT and L175D mouse E-cadherin were the same, although L175D reduces the sizes of cadherin clusters larger than 20 nm (58).…”
Section: Discussionmentioning
confidence: 69%
“…Based on STORM images, clusters of the mouse E-cadherin L175D cis mutant expressed on A431 cells were significantly smaller than WT E-cadherin (58). Fig.…”
Section: Colo 205 Treatment With Staurosporine Increases the E-cadhermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with E-cadherin (E-cad)-coated substrates have revealed the existence of E-cad nanoclusters as fundamental units for cell-cell adhesion, and their existence has been confirmed by super-resolution imaging of mammalian cellcell contacts (Wu et al, 2015;Strale et al, 2015), as well as in Drosophila (Truong Quang et al, 2013). In addition, both E-and N-cad-coated deformable pillars allow the measurement of the traction forces that are exerted by a single cell across cadherin bonds.…”
Section: Ecm Sensingmentioning
confidence: 99%